The Problematic of Language Interference in Teaching Speaking Skills to Students of IAI Hamzanwadi NW East Lombok - Sugiara, Lalu Rahmat; Setiyawan, Agung; Haris, Yogi Sopian; Fatihin, Muhammad Khairul (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2025)
The teaching of Maharah al-Kalam (speaking skills) at the Islamic Institute of Hamzanwadi Nahdlatul Wathan, East Lombok, faces various issues related to language interference. These challenges arise when students struggle to express ideas and thoughts spontaneously in Arabic due to the influence of their mother tongue (Indonesian) and regional languages. This study aims to deeply examine the issues of language interference in teaching Maharah al-Kalam at the Islamic Institute of Hamzanwadi Nahdlatul Wathan, East Lombok. It seeks to identify the forms of language interference occurring and analyze the underlying factors. The research employs a field research method with a qualitative approach, involving direct observation, in-depth interviews, documentation, and analysis of student speech transcripts. The study reveals the complexity of linguistic challenges faced by students in mastering Arabic speaking skills. Language interference was identified in three dimensions: phonology, syntax, and vocabulary, driven by limited exposure to Arabic, traditional teaching methods, and the dominance of the mother tongue. The impacts of interference include a decline in students’ confidence and reduced quality of Arabic communication. To address these issues, the research proposes comprehensive solutions, such as developing practical teaching methods, raising linguistic awareness, employing a contrastive approach, and implementing intensive training techniques like drilling and role-playing.